The Effect of Debt Policy, Profitability and Liquidity on Dividend Policy - Khairi, Himmatul (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2024)
The purpose of this study is to investigate the impact of debt policy (measured by Debt to Equity Ratio), profitability (measured by Return on Asset), and liquidity (measured by Current Ratio) on dividend policy (measured by Dividend Payout Ratio). The study focuses on companies listed on the Indonesia Stock Exchange (IDX) under the Jakarta Islamic Index 70. Secondary data from financial statements spanning three consecutive years (2019 to 2021) were utilized for the analysis. The research employed purposive sampling, resulting in a sample of 44 companies, and multiple linear regression analysis was employed to test the research hypotheses. The findings indicate that, collectively, debt policy, profitability, and liquidity significantly influence the dividend policy of companies within the Jakarta Islamic Index from 2019 to 2021. However, when considering individual variables, only profitability demonstrates a significant impact on dividend policy among the listed companies from 2019 to 2021